Patterns and measures of digitalisation in business unit communication. (19th July 2005) - Tyrvainen, Pasi; Kilpelainen, Turo; Jarvenpaa, Matti
Business information systems have radically transformed business processes with the emergence of new digital communication forms. However, employees still communicate verbally and on paper as well. This study analyses internal and external communication of three business units through an analysis of 60 to 150 communication genres in each. According to the results, 51% to 59% of internal stored communication was digital adding up to 52–58% when external communication was included. The degree of internal digitalisation correlated better with the outbound than with the inbound communication. In one case, a publication pattern dominated the communication. In another case, a digitalised supply chain pattern drove the digitalisation. In the third case, the internal verbal coordination and the publication pattern were both present. These results suggest that the dominating patterns have major impact on media selection in organisations and guide the digitalisation and emergence of new business information systems.